Numerical study on effect of vortex generator for t-junction pipe flow - Alazemi, Hamad R Dh A S (2019)
Application of Computational fluid dynamics (CFD) in studying T-Junction water pipe flow have been growing steadily. This is due to the fact that experimental work will cost more time and money. In Kuwait however, the CFD tool is not fully utilised in the T- Junction case due to lack experts to perform the CFD work. The current work focused on the CFD simulation on the T-Junction water pipe system that is available in Kuwait. The objective of the work is to investigate the fundamental physical mixing effects of the Kuwaiti T-Junction pipe and investigate the effects of the flow control device inside the T-Junction. The RANS equation was used as the governing equation. The standard k- epsilon model will be used for the turbulent flow of the water pipe. Second order discretization method was used to solve the non-linear RANS equations. The CFD results have been validated with the published experimental data with good agreement. From the baseline simulation, it is found that the physics of water flow shows that there is significant reverse flow at the downstream of the T-junction pipe. From the parametric study, three cases have been tested namely case with two vortex generators, four vortex generators, and eight vortex generators. From the results, it was found that the case with four vortex generators outperformed the other cases. The area of the reverse flow have been decreased significantly. Another parametric study was the size of the vortex generator. It was found that the best size was the 75 mm. The last parametric study was the magnitude of the water pipe flow. From the results, it was found that the vortex generator performed the best at the magnitude of 5m/s.